2022
DOI: 10.1017/s0031182022001263
|View full text |Cite
|
Sign up to set email alerts
|

Long-term temporal trends in gastrointestinal parasite infection in wild Soay sheep

Abstract: Monitoring the prevalence and abundance of parasites over time is important for addressing their potential impact on host life histories, immunological profiles and their influence as a selective force. Only long-term ecological studies have the potential to shed light on both the temporal trends in infection prevalence and abundance and the drivers of such trends, because of their ability to dissect drivers that may be confounded over shorter time scales. Despite this, only a relatively small number of such s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Population density likely drives greater helminth infection by driving greater indirect contact: that is, if more individuals are inhabiting and shedding parasites in higher-density areas, the parasites will achieve a higher concentration on the pasture, thereby driving greater individual-level exposure in these areas. This corroborates prior knowledge concerning the role of population density in driving infection in this population via greater environmental exposure [25,26] – and offers an explanation for the previously observed positive correlation between strongyle count in lambs and preferred vegetation, which is likely to coincide with areas of high host density [30]. However, our use of individual-level (spatial) density metrics allowed us to pick up much finer-scale relationships between density and infection, and thereby detected several more such relationships than previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Population density likely drives greater helminth infection by driving greater indirect contact: that is, if more individuals are inhabiting and shedding parasites in higher-density areas, the parasites will achieve a higher concentration on the pasture, thereby driving greater individual-level exposure in these areas. This corroborates prior knowledge concerning the role of population density in driving infection in this population via greater environmental exposure [25,26] – and offers an explanation for the previously observed positive correlation between strongyle count in lambs and preferred vegetation, which is likely to coincide with areas of high host density [30]. However, our use of individual-level (spatial) density metrics allowed us to pick up much finer-scale relationships between density and infection, and thereby detected several more such relationships than previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The wild Soay sheep ( Ovis aries ) of St Kilda have been studied since 1985, with individual-based measurements of behaviour, life history, and parasitism throughout this time [24]. They host a diversity of gastrointestinal parasites, all of which have some environmental phase in between hosts and achieve reinfection through reingestion [25,26]. They also host sheep keds ( Melophagus ovinus ): wingless ectoparasitic flies that achieve transmission through direct contact [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal changes in helminth burdens are also well recognized, although most such studies have been conducted over very short time spans, usually just 1–2 years (Lewis, 1968; Langley & Fairley, 1982; O'Sullivan et al , 1984; Montgomery & Montgomery, 1988, 1989, 1990; Gregory, 1992; Abu-Madi et al , 1998, 2000; Behnke et al , 1999). More recently, attention has shifted to perturbation experiments in wild mice (Ferrari et al , 2004; Pederson & Grieves, 2008; Knowles et al , 2013; Pederson & Antonovics, 2013) and to monitoring long-term changes (Grzybek et al, 2015a: Behnke et al , 2019, 2021; Sweeny et al , 2021a; Hayward et al , 2022; Wood et al , 2023) Both approaches have revealed remarkable stability of some helminth species, usually the core species, as well as marked fluctuations in others reflecting between year cycles and responses to perturbation, temporally declining worm burdens, as well as complete loss and acquisition of new species.…”
Section: Introductionmentioning
confidence: 99%